2021
DOI: 10.3390/cancers14010055
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Stem Cell Transplantation in Multiple Myeloma

Abstract: The development of new inhibitory and immunological agents and combination therapies significantly improved response rates and survival of patients diagnosed with multiple myeloma (MM) in the last decade, but the disease is still considered to be incurable by current standards and the prognosis is dismal especially in high-risk groups and in relapsed and/or refractory patients. Allogeneic hematopoietic stem cell transplantation (allo-SCT) may enable long-term survival and even cure for individual patients via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 100 publications
(180 reference statements)
1
21
0
Order By: Relevance
“…The potential role of immunotherapy for MM was initially established with the graft-versus-myeloma effect of allogeneic hematopoietic cell transplantation (allo-SCT). Allo-SCT has been shown to induce long-term remission and potential cure in a subset of MM patients, which is thought to be due to anti-myeloma activity of graft alloreactive lymphocytes ( 2 , 21 – 23 ). The efficacy of this approach was further underscored by success of donor lymphocyte infusion (DLI) for patients who relapsed after allo-SCT ( 24 ).…”
Section: Allogeneic Stem Cell Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential role of immunotherapy for MM was initially established with the graft-versus-myeloma effect of allogeneic hematopoietic cell transplantation (allo-SCT). Allo-SCT has been shown to induce long-term remission and potential cure in a subset of MM patients, which is thought to be due to anti-myeloma activity of graft alloreactive lymphocytes ( 2 , 21 – 23 ). The efficacy of this approach was further underscored by success of donor lymphocyte infusion (DLI) for patients who relapsed after allo-SCT ( 24 ).…”
Section: Allogeneic Stem Cell Transplantmentioning
confidence: 99%
“…To reduce treatment-related morbidity and mortality and increase the pool of allo-SCT eligible patients, non-myeloablative or reduced-intensity conditioning (RIC) allo-SCT has similarly been used ( 25 27 ); however, this strategy has been associated with increased risk of relapse, highlighting the importance of initial high-dose cytotoxic conditioning for durable response and remission ( 2 , 25 ). High-dose chemotherapy with autologous transplant followed by RIC allo-SCT has been evaluated to potentially balance these two approaches, but studies have demonstrated some late relapses as well as unclear efficacy or reduced survival when compared with tandem autologous transplantation ( 2 , 23 , 25 ). While allo-SCT may still have a potentially curative role in a curated subset of patient ( 28 ), risks related to infection and GVHD remain significant.…”
Section: Allogeneic Stem Cell Transplantmentioning
confidence: 99%
“…It has already provided the basis for a number of advanced technologies, such as the breeding of transgenic animals, including those tolerant to diseases [ 1 ] or producing biologically active substances [ 2 ], somatic cell nuclear transfer (SCNT)-based animal cloning [ 3 ], and in vitro production of bioartificial tissues and organs [ 4 ]. Stem cell transplantation (stem cell therapy) and stem cell-based tissue engineering are the keystones of regenerative medicine, an innovative trend in medicine with the potential to become a new healthcare industry [ 5 , 6 , 7 , 8 , 9 ]. New stem cell therapy applications, such as hematopoietic and mesenchymal stem cell transplantation in patients with hematological malignancies or autoimmune diseases, are emerging [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…NK cells recover within 3-4 weeks after HSCT, but until 6 months posttransplant there is an imbalance between mature and immature NK cells in the peripheral blood. However, as the first reconstituted lymphocyte subset after transplantation, early NK cell reconstitution plays a critical role in controlling potential relapse in allogeneic HSCT 48,49 . Recovery of the adaptive immunity takes much longer.…”
Section: Immune Reconstitution After Haematopoietic Stem Cell Transpl...mentioning
confidence: 99%
“…Nevertheless, it was clearly an effect of the HSCT. Furthermore, the fact that the patients already received several treatment lines (average 3, range 2 to 7) could also be of influence to the lack of response, since the best responses of allogeneic HSCT in MM in general are seen when it is used in an earlier course of the disease 49 .…”
Section: Haploidentical Stem Cell Transplantation As Alternative Dono...mentioning
confidence: 99%